Adhesive bonding in composite structures for aerospace applications - Shashi Bhushan Kumar (2008)
Composite bonded scarf and lap joints made from unidirectional carbon fibre re-inforced plastic and various type of aerospace grade adhesives (AF-163-2 from 3M, Redux 322, Redux 335K and Redux 319A were studied.